Comparison of dental caries status among visually impaired children based on risk factors: a cross-sectional study - Mayasari, Yufitri; Darwita, Risqa Rina; Setiawati, Febriana; Novrinda, Herry (Universitas Padjadjaran, 2025)
Introduction: According to the World Health Organization (WHO), over 2.2 billion people globally are affected by visual impairment, which significantly affects their dental and oral hygiene behaviors. Consequently, the prevalence of dental caries among visually impaired children remains high, primarily due to challenges in maintaining proper hygiene. This study aims to analyze differences in dental caries status among visually impaired children based on risk factors. Method: The study procedures were carried out using a cross-sectional design. The sample population comprised 94 students at the National Special School (SLB) A Pembina, who were selected using a purposive sampling method. Data collection was conducted in 2 stages. The first stage involved gathering information on risk factors through interviews regarding toothache experience, visits to the dentist, tooth brushing frequency, and fluoride toothpaste use. The second stage consisted of dental and oral examinations conducted by five trained investigators. Results: The overall prevalence of dental caries among visually impaired children was 42.6%, with a deft/DMFT index of 1.05/0.8. In addition, there were significant differences in dental caries status based on risk factors, such as toothache experience (p=0.001, ≤0.05, Pearson’s Chi-square, 95% CI), visits to the dentist (p=0.000, ≤0.05, Pearson’s Chi-square, 95% CI), tooth brushing frequency (p=0.000, ≤0.05, Pearson’s Chi-square, 95% CI), and fluoride toothpaste use (p=0.000, ≤0.05, Pearson’s Chi-square, 95% CI). Conclusion: Based on these results, the prevalence of dental caries among visually impaired children is relatively high. Caries experience is significantly associated with toothache experience, visits to the dentist, tooth brushing frequency, and fluoride toothpaste use.